2017
DOI: 10.1027/0227-5910/a000422
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Online Self-Monitoring to Support Clinicians Manage Risk of Suicide in Youth Depression

Abstract: The online tool facilitates the quick exchange of key information about suicide risk, allowing clinicians to immediately address this. This level of responsiveness is likely to improve treatment outcomes. The brief version allows full integration into clinical practice to support clinicians managing those at risk of suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…As Perry et al (2016) noted in their SR, other areas of suicide prevention, such as screening young people for risk of suicide, are beginning to use web-based platforms to deliver services 64. The use of ‘real time’ monitoring and intervention provided via handheld devices to support young people ‘in the moment’ has been flagged as important for overcoming difficulties mental health services have with responding to fluctuating SI and episodes of SH and SA 65. Despite the trial by Tighe and colleagues not being eligible for inclusion in this review, the Ibobbly intervention is worthy of further exploration in an adolescent and youth population (under 25 years) given its accessibility 35…”
Section: Discussionmentioning
confidence: 99%
“…As Perry et al (2016) noted in their SR, other areas of suicide prevention, such as screening young people for risk of suicide, are beginning to use web-based platforms to deliver services 64. The use of ‘real time’ monitoring and intervention provided via handheld devices to support young people ‘in the moment’ has been flagged as important for overcoming difficulties mental health services have with responding to fluctuating SI and episodes of SH and SA 65. Despite the trial by Tighe and colleagues not being eligible for inclusion in this review, the Ibobbly intervention is worthy of further exploration in an adolescent and youth population (under 25 years) given its accessibility 35…”
Section: Discussionmentioning
confidence: 99%
“…Young people with depression commonly experience suicidal ideation and engage in self-harm ( 23 ) and require support to monitor symptoms outside of face-to-face treatment ( 24 ). During a scoping/generative phase (Figure 2 ), SH and colleagues engaged young people with lived experience of self-harm individually to understand their needs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinicians are specifically instructed to monitor the emergence of suicidal ideation once a week for 4 weeks, and biweekly thereafter, upon commencing antidepressant medication, due to the known risks of this adverse outcome for young people taking antidepressants [ 6 , 8 ]. The accurate reporting of symptoms facilitates therapeutic monitoring [ 9 ] in terms of enhancing clinicians’ knowledge about the clients’ symptoms and risk, which can have a positive impact on treatment planning [ 10 , 11 ]. Young people have been shown to have faster symptom improvement when their clinicians receive feedback about treatment progress [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of technology in clinical practice has been shown to be acceptable to users and health professionals [ 35 , 36 ]. There is emerging evidence that young people may, in some circumstances, be more comfortable with technology over face-to-face intervention with therapists [ 37 ], and studies have shown that rates of disclosure of mental health difficulties and suicidal ideation are higher when paper and pencil or Web-based approaches are used relative to face-to-face assessment [ 9 , 10 , 38 - 42 ]. Similarly, young people are particularly enthusiastic users of smartphones and various mobile phone apps [ 43 , 44 ], and consider smartphones an acceptable form of support [ 45 - 47 ].…”
Section: Introductionmentioning
confidence: 99%